Analysis of Islamic Religious Education Teachers' Motivation in Organizing Dhuha Prayer in Congregation - Fauzan, Fajri; Endis Firdaus; Achmad Faqihuddin (Medina-te : Jurnal Studi Islam, 2024)
This study examines the motivation of Islamic Religious Education (PAI)teachers in organizing congregational Dhuha prayers in schools in Bandung City and its impact on student development. Using a qualitative approach, this study involved in-depth interviews with PAI teachers and students, as well as direct observation of Dhuha prayer activities. The results of the study show that the motivation of PAI teachers comes from intrinsic factors, such as a sense of responsibility as a religious educator and a desire to instill spiritual values, as well as extrinsic factors, including school policy support and parental appreciation. The implementation of congregational Dhuha prayers has proven to have a positive impact on improving student discipline, especially in time management, strengthening worship habits, and increasing Qur'an literacy. This activity also plays a role in shaping the religious character of students and creating a school environment that is conducive to the development of religious values. Although limited to the context of the city of Bandung, this study provides important insights into the integration of religious practices in formal education. It is recommended for further research to expand geographical coverage, use mixed methods, and conduct longitudinal studies to understand the long-term impact of the Dhuha prayer program on the academic and spiritual development of students.